Cu/CGO cermet based electrodes for Symmetric and Reversible Solid Oxide Fuel Cells. (7th May 2020) - Carollo, G.; Garbujo, A.; Bedon, A.; Ferri, D.; Natile, M.M.; Glisenti, A.
Abstract: Cu-based cermets suitable for electrodes in Symmetric and Reversible Solid Oxide Fuel Cells (SR-SOFCs) based on the Cerium Gadolinum Oxide (CGO) electrolyte were developed and successfully tested in the intermediate temperature range (600–800 °C). The Cu/CGO cermets were prepared by means of a self-combustion based citrate procedure and the effects of synthesis conditions were studied. Characterization of the Cu/CGO nanocomposites by XPS, XRD, SEM, TPR suggested that this procedure allows obtaining highly dispersed CuO on the cerium gadolinium oxide. Conversion higher than 80% was observed above 600 °C in methane total oxidation. Synthesis parameters affected both properties and catalytic performance. The behaviour under redox conditions was studied by operando high-energy XRD under oscillating H2 /O2 feed. Reducing conditions converted CuO into Cu(0) passing through an intermediate Cu2 O phase while increasing the conductivity and the reactivity. This structural modification was completely reversible. The high stability, reversibility, catalytic activity and electrochemical performance make these electrodes promising for SR-SOFCs. Highlights: A new procedure for preparation of high performance cermet was optimized. Highly dispersed CuO in CGO is obtained by complexation with citrates. Effect of pH on complexation, dispersion, catalytic performance stability is investigated. Structural stability/reversibility in redox conditions studied by High Energy XRD (ERSF). Electrocatalytic and catalytic activities compared and related to the synthesis parameters.